Assessment of left atrial function provides incremental value: the left atrial volumetric/mechanical coupling index in patients with chronic kidney disease - Ji, Liqin; Gao, Xue; Xiao, Weiwei; Yu, Shaomei (Frontiers in Cardiovascular Medicine, 2024)
Background Heart failure is a common cause of adverse cardiovascular outcomes in patients with chronic kidney disease (CKD). Left atrial (LA) characteristics are thought to be involved in the development of heart failure. However, LA assessment is complex. Though a variety of parameters have been defined, there is no single parameter that best defines LA function. Pilot data indicate that left atrial volumetric/mechanical coupling index (LACI) may be useful, but data with CKD are lacking. Aim The objective of this study was to define LACI in a cohort of patients with CKD and to assess its value in evaluating LA function and predicting heart failure. Methods A cohort of patients with CKD was enrolled at our hospital between 2021 and 2023. Follow-up was performed for heart failure. LACI is a volumetric to mechanical coupling index, calculated as the ratio of the LA volume index to the tissue-Doppler myocardial velocity at atrial contraction. Spearman’s rank correlation or Pearson’s correlation was used to calculate the correlation between LACI and echocardiographic/hemodynamic variables. Receiver operating characteristic curve (ROC) analysis was utilised to derive the area under the curve (AUC) for LACI, LVGLS, LASr, LASct and LASI for the detection of heart failure. Kaplan-Meier survival curves were employed to compare clinical outcomes based on LACI thresholds. A multivariable logistic regression analysis was employed to assess the relationship between risk factors and elevated LACI. Cox proportional hazards regression was used to identify risk factors for heart failure. Results LACI showed a positive correlation with NT-proBNP, CK-MB, LAVI, E/e’ and LASI (r = 0.504, 0.536, 0.856, 0.541 and 0.509, p < 0.001); and a negative correlation with LASr (r = −0.509, p < 0.001). On the ROC analysis for the determination of heart failure, the AUC of LACI was comparable to those of LVGLS (0.588 vs. 509, p = 0.464), LASr (0.588 vs. 0.448, p = 0.132), LASct (0.588 vs. 0.566, p = 0.971) and LASI (0.588 vs. 0.570, p = 0.874). The cardiovascular risk factors increased by LACI were age, BMI, diabetes, triglycerides, LA size, LASr, LASI, E/A, E/e’ and EF (p < 0.05). During a median follow-up of 16 months (range, 6–28 months), the event-free survival curves demonstrated a higher risk of heart failure in the group with LACI > 5.0 (log-rank test: P < 0.001). LACI > 5.0 was an independent predictor of heart failure [OR: 0.121, 95% CI (0.020–0.740), p = 0.022]. Conclusion LACI may prove to be a valuable tool for assessing LA function in patients with CKD, and could be integrated into the routine assessment of LA for the purpose of prognostic assessment and clinical decision-making in patients with CKD.